Pengaruh Bauran Pemasaran dan Store Atmosphere Terhadap Keputusan Pembelian Konsumen Rumah Makan Dapur DK (Dewi Kahyangan) Jombang - Yuliana Yuliana (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
This research aims to understand the effect of mix marketing and store atmosphere both partially and simultaneously to the consumer phurchase decision. It is a quantitative reseach by using quesionaire as an instrument. The reseach subject is consumer who did purchasing DK restaurant, samples which is chosen by incidental sampling. The datawas analiyzed by using multiple regression. The result shows that (1) Mix marketing variable affech positively to the consumer purchase decision whit t-test 10,882>t tabel 0,150 and signifikan level 0,000. (2)Store atmosphere variable affect positively to the consumen purchase decision with test t tabel 4,468> t tabel ,150 and signifikan level 0,000 (3) mix marketing variable and store atmosphere variable simultaneously affects to the consumer perhacse decision with the-test 102,632 > F tabel. Keywords: Mix Marketing; Store Atmosphere; Purchase Decision